PENEGAKAN HUKUM TINDAK PIDANA KEPABEANAN TERHADAP PAKAIAN BEKAS (BALLPRESS)/CAKAR DI WILAYAH PALU SULAWESI TENGAH - Hanker, Force (Tadulako Master Law Journal, 2020)
AbstractThe problem studied were the law enforcementof the customs of used secondhand clothesat the office Supervision and Customs Service of Madya Pabean C Type Pantoloan and the obstaclesin criminal law enforcement for the circulation of secondhand clothes that affected the society of Palu. This research was empirical legal research that used primary dan secondary data is then presented in the form of inductive thinking patterns, namely the specific things to general things. The results of the research find that the office Supervision and Customs Service Of Madya Pabean C Type Pantoloan had carried out several law enforcement on the crime of secondhand clothes covering preventive and repressive law enforcement. Preventive law enforcement such as carrying out observation of importers data, distributing brochures about the dangers of secondhand clothes, collaborating with related parties that are the health Office and industry and trade service, and patrolling parts in the working area. Depressive law enforcement such as arresting the perpetrators of customs offens, confiscation of evidence in the form of secondhand clothes and destruction of secondhand clothes. Obstacles faced by customs in making legal efforts to the crime of secondhand clothes namely the limitation of ships in conducting patrols, lack of human resource that are not in accordance with the extensive of working area, weak legislation, law enforcement officers, society are interested in used clothing and proof because they have to present key witnesses.Keywords : law enforcement, customs, secondhand clothes